Ovarian reserve and pregnancy prognosis in in vitro fertilization - Vargas-Tominaga, Luis (2025)
Introduction: The woman’s age and ovarian reserve are the most important factorsin fertility treatment. Ovarian reserve can be calculated through antral follicle count(AFC) with vaginal ultrasound, providing valuable information on the pregnancyprognosis in assisted reproduction. Objective: To define the significance of AFC in thepregnancy prognosis in in vitro fertilization. Methods: Retrospective observationalstudy in which the clinical records of 508 infertile patients who underwent in vitrofertilization at the Centro de Fertilidad y Ginecología del Sur from December 2005 toApril 2024 were reviewed. The clinical pregnancy rate in women with AFC ≥ 5 and inthose with AFC < 5 is analyzed and compared with the differences found accordingto age. Results: The clinical pregnancy rate in women with AFC ≥ 5 was 35.2%, while itwas 14.3% in women with AFC < 5 (p = 0.0236), and was 41.9% in patients < 35 yearsand 27.2% in those ≥ 35 years (p = 0.0005). Differences in clinical pregnancy rate aremore transcendent when considering AFC rather than age (Odds Ratio: 3.3 versus1.9, respectively). Conclusions: Patients with AFC < 5 have three times lower clinicalpregnancy rate in IVF than those with greater ovarian reserve.